VERBAL-VISUAL APPRAISAL SYSTEM IN NEWS REPORTING THE COLLAPSE OF KARTANEGARA BRIDGE: AN APPRAISAL ANALYSIS OF HARD NEWS IN KOMPAS - KOMARAWAN, Yulizar (2012)
This study investigates how the collapse of Kartanegara Bridge is verbally and visually appraised in Kompas and how verbal and visual Appraisal systems construe Kompas' position toward the issue. The study is based on a qualitative method using verbal Appraisal Theory proposed by Martin and his colleagues (Martin, 1997, 2000; White, 1998, 2003, 2005, 2006, 2011; Martin and White, 2005; Hood, 2010), visual Appraisal Theory by Economou (2009), and visual 'grammar' by Kress and van Leeuwen (2006) to analyze the data. The data include two hard news reports and photos published on 28 and 29 November 2011. The study finds that the collapse of the bridge is verbally and visually appraised negative with respect to action of the suspects and the Minister of Public Works that caused a danger and could not recognize the reasons for the collapse and positive with respect to action of people committing to help and investigate. The study also finds that the verbal and visual Appraisal systems construe Kompas' position either positive or negative via the configuration of judgment, graduation, and engagement values across the (verbal and visual) texts. Keywords: verbal Appraisal Theory, visual Appraisal Theory, hard news, news photos, visual 'grammar'.